Analysis of Integrated Marketing Communication Strategies in Building Brand Awareness (Case Study of SAMASE Brand in Bengkalis) - Rahmadhani, Putri Fajrin; Asra, Yunelly (Politeknik Negeri Bengkalis, 2024)
Integrated marketing strategy allows brands to consistently transmit their brand message and image through various channels, which helps build strong brand awareness among consumers. This research aims to analyze Integrated Marketing Communication strategies that can be used to build brand awareness of SAMASE brand products, especially among the people of Bengkalis. The research method in this study is descriptive qualitative. Data collection was done through observation, interviews, and documentation. Data analysis techniques uses data collection, data reduction, and conclusion drawing. The research results found that Ila Jannah Moslem Store uses various IMC elements. Specifically, Advertising is done through social media channels. Sales promotions are carried out by providing discounts, while Personal Selling is through providing direct sales services. Word of Mouth is facilitated by consumers spreading positive messages about SAMASE products. Through these four IMC elements, Ila Jannah Moslem Store succeeded in building brand awareness and achieving a Top of Mind level. The conclusion of this research for Ila Jannah Moslem Store is to focus more on increasing promotions and increasing product excellence. In addition, it is also necessary to maximize the use of social media and e-commerce platforms to reach a wider target market and build strong relationships with consumer.